Performance analysis of quad-port UWB MIMO antenna system for Sub-6 GHz 5G, WLAN and X band communications - Ismail, Mohd Muzafar; Al Gburi, Ahmed Jamal Abdullah; Pandya, Killol; Upadhyaya, Trushit; Patel, Upesh; Sorathiya, Vishal; Pandya, Aneri (Elsevier B.V., 2024)
A quad-port Multiple Input Multiple Output Antenna with high isolation is presented in this paper. The MIMO design is intended to receive Ultra-Wide Band response to target various wireless applications. The engineered model has 40 x 40 × 1.6 mm3 electrical dimensions. A single antenna achieves size compactness due to an appropriate inclusion of vertical and horizontal conductive strips. Additionally, a diagonal radiating strip is shaped and pooled with the patch geometry. A similar design is positioned orthogonally with each other to receive diversified performance. The four conducting ports are positioned with an appropriate minimum distance to lower down the possible mutual coupling. A partial ground plane having border geometry has been incorporated to receive the ultra-wide band response. An additional plus-sign shaped conducting strips are provided and united with ground lines for isolation enhancement. The MIMO system exhibits ultra-wide frequency response from 3.20 GHz to 13.40 GHz with adequate isolation below − 20 dB and an impedance bandwidth of 10.20 GHz. The proposed structure provides an overall gain of 2 dBi having above 80 % efficiency. The presented radiator exhibits excellent MIMO diversity response achieving minimal mutual coupling effect. The other output parameters such as envelope correlation coefficients<0.05, diversity gain of nearly 10 dB, mean effective gain<0.2 dB, and channel capacity loss<0.1 bits/sec/Hz were obtained. The proposed design has been simulated in High Frequency Structure Simulator (HFSS) software. The developed MIMO antenna has been analyzed through VNA N9912A. An encouraging correlation between the software generated and actual responses was observed. The strong agreement between actual results and software results shows the design potential for wireless communications. The highly isolated MIMO system registers its potential for sub-6 GHz 5G, WLAN, and X Band communications.